2008
DOI: 10.1086/591133
|View full text |Cite
|
Sign up to set email alerts
|

A World Wide Web–Based Antimicrobial Stewardship Program Improves Efficiency, Communication, and User Satisfaction and Reduces Cost in a Tertiary Care Pediatric Medical Center

Abstract: The World Wide Web-based antimicrobial approval program led to improved communication, more-efficient antimicrobial administration, increased user satisfaction, and significant cost savings. Integrated tools, such as this World Wide Web-based antimicrobial approval program, will effectively enhance antimicrobial stewardship programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 18 publications
1
78
0
1
Order By: Relevance
“…Antibacterial ASPs in pediatric centers worldwide have recently been reported (45)(46)(47). However, as in the adult population, the relative infrequency of antifungal use compared with the use of antibacterial drugs has led to the development of antifungal stewardship being less forthcoming.…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial ASPs in pediatric centers worldwide have recently been reported (45)(46)(47). However, as in the adult population, the relative infrequency of antifungal use compared with the use of antibacterial drugs has led to the development of antifungal stewardship being less forthcoming.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction of clindamycin 48 (or clindamycin, cefotaxime, and vancomycin 27 ) has been shown to control outbreaks of nosocomial C difficile-associated diarrhea and VRE, respectively. More recently, Internetbased antimicrobial restriction programs 49,50 and a computerized (electronic) approval system 51 have been demonstrated to reduce antibiotic use at tertiary hospitals. Some studies have reported increased antibiotic drug susceptibilities after implementation of institutional preauthorization policies, 45,46,51 and at least 1 reported a decreased incidence of ceftazidime-resistant Klebsiella species after instituting a preapproval policy for cephalosporins.…”
Section: Formulary Restriction and Preauthorizationmentioning
confidence: 99%
“…Ensuring that hospitalized patients receive the right antimicrobial, at the right dose, at the right time, and for the right duration has been shown to reduce mortality, 1 reduce the risks of Clostridium difficileassociated diarrhea, 2 shorten length of stay, 3 reduce overall antimicrobial resistance within the facility, 4 and save money. 5 Yet despite these benefits, antimicrobial stewardship programs and interventions are far from the norm in US hospitals. There are 2 important myths about antimicrobial stewardship that likely contribute substantially to the gap between the recognized benefits and implementation of stewardship interventions.…”
mentioning
confidence: 99%